(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article describes the irrigated winter grain state and technology cultivation in Uzbekistan. It was carried out a comparative analysis of grain continuous bed sowing efficiency in rows with respect to traditional sowing. The row-sowing method innovative technology of sowing in the beds was recommended, which ensures land resources conservation, an increase in yield and a decrease in material costs.